Attitudes, Confidence in Practices and Perceived Barriers Towards the Promotion of Tobacco Cessation among Clinical Dental Undergraduates in Sri Lanka - Medawela, R M Sumudu Himesha B; D L Ratnayake, Dugganna Ralalage; Premathilake, L K Nadeesha; Jayasinghe, Ruwan Duminda (Asian Pacific Journal of Cancer Care, 2021)
Introduction: This study aimed to assess attitudes, confidence in practices and perceived barriers toward the promotion of tobacco cessation in the dental setting among clinical dental students in Sri Lanka. Methods: Role of dental schools on moulding future dental professionals with regards to education on tobacco cessation promotion is remarkable. A cross-sectional descriptive study was conducted on all the dental students from clinical years in 2018 using a self-administered structured questionnaire. Ninety-four per cent of the dental students from clinical years of faculty of dental sciences, University of Peradeniya, Sri Lanka completed the questionnaire (65% Females and 35 % Males) with a mean age of 24.65+ 2.24 years. Results: Clinical dental students possessed positive attitudes towards the professional responsibility of dentists in tobacco cessation whilst only 34% strongly agreed counselling offered in the dental setting has an impact on the same. More than half of the students remained neutral or disagreed the fact that nicotine replacement is within the scope of dentistry. Respondents expressed their confidence in tobacco cessation counselling. They identified “patients’ disinterest in receiving advice” as the main barrier to perform tobacco cessation practices in the dental setting. It is prudent to include formal education on tobacco cessation to the undergraduate curriculum of dental students to alleviate misconceptions related to practices of tobacco cessation in dental settings. Conclusion: It is of prime importance to identify training needs related to tobacco cessation promotion among dental undergraduates and compose a separate training module for them.